Peran dan Pengaruh Filsafat dan Logika dalam Metode Istinbāth Hukum Islam - Abbas Arfan (Ulumuna, 2015)
Muslim scholars argue that the relationship between usul fiqh, philosophy, and logic is ‘alāqah ihtiyājiyyah manhājiyyah (methodological need relationship) because the legal ground in the theory of usul fiqh is not only derived from the scripture (naqlī) such as the Qur’an and Hadits but also from logic (‘aqlī). In order to have more understanding in the textual reason (naqlī), it requires logical reason or logical competence. This paper attempts to analyze critically and comprehensively such relationship so it will be revealed the position of philosophy and logic in Islamic law. This is important since Muslims still view that philosophy and logic are irrelevant with Islam. This study demonstrates that the relationship between philosophy and logic with Islamic law is very strong because the methodology of Islamic law (usul fiqh) accommodate them. So it is a methodological relationship. Thus, claiming that these two disciplines are forbidden in Islam, as Muslims may assume, is untenable. In contrast, they are an important element in the Islamic legal system. DOI: http://dx.doi.org/10.20414/ujis.v19i1.1252